A new species of the vitismin cockroach genus Perspicuus Koubová, 2020 from the Late Cretaceous (Santonian) of Hungary - Szabó, Márton; Sendi, Hemen; Ősi, Attila (Zootaxa, 2024)
Mesozoic amber cockroaches are rare compared to sedimentary imprints and are only known from Myanmar, Lebanon, France, Russia and USA. Perspicuus csincsii sp. n. from the Late Cretaceous (Santonian) ajkaite amber of Hungary with very long cerci, cup-like terminal palpomere of the maxillary palp and fully carinated legs, is clearly distinguished from all other Vitisminae species by the unique, black forewing with small light-coloured dots/stripes and the absence of pubescence on the wings (autapomorphies). The second cockroach described from the ajkaite adds important data to the distribution pattern of Vitisminae during the Late Cretaceous and further highlights the similarity of the ajkaite and burmite biotas.